A call to action: Feasible strategies to reduce the discard of transplantable kidneys in the United States. Issue 9 (4th July 2020) - Stewart, Zoe A.; Shah, Shimul A.; Formica, Richard N.; Kandaswamy, Raja; Paramesh, Anil S.; Friedman, Jessica; Squires, Ronald; Cooper, Matthew; Axelrod, David A.
Abstract: Changes to the United States kidney allocation system targeted at reducing organ discard have failed to improve organ utilization. High Kidney Donor Profile Index kidneys continue to be discarded at high rates as a result of the regulatory and financial barriers to widespread utilization of these organs. However, there are potential changes to clinical practice that could improve organ utilization. Expediting the time from initial offer to final organ acceptance would reduce cold ischemic time and should improve utilization. Implementation of procurement biopsy standards to avoid biopsy of low risk organs may prevent organ discards due to inaccurate data or excessive cold ischemia time. Further, standardization of procurement biopsy pathological interpretation coupled with electronic accessibility would enable early acceptance of difficult to transplant organs. These changes to allocation practice patterns are vital given proposals to expand the geographic sharing of deceased donor kidneys. Implementation of new allocation policies must be evaluated to ensure they result in higher transplant rates and acceptable post‐transplant outcomes.